Foraging behaviour and habitat use by Indian Yellow-nosed Albatrosses (Thalassarche carteri) breeding at Prince Edward Island. (2nd October 2018) - Makhado, A. B.; Crawford, R. J. M.; Dias, M. P.; Dyer, B. M.; Lamont, T.; Pistorius, P.; Ryan, P. G.; Upfold, L.; Weimerskirch, H.; Reisinger, R. R.
ABSTRACT: Demographic parameters of wild animals are often closely associated with their foraging distribution and behaviour, and understanding these attributes can assist in identifying causes of population changes. The Indian Yellow-nosed Albatross ( Thalassarche carteri ) is endangered but little information is available on its at-sea distribution and behaviour. It breeds only in French (Iles Amsterdam, St Paul, Kerguelen and Crozet) and South African (Prince Edward Island, PEI) territories in the south-west Indian Ocean, with PEI supporting about 20% of the global population. This study aimed to investigate the at-sea distributions of adult Indian Yellow-nosed Albatrosses provisioning chicks at PEI and to compare them with distributions of Yellow-nosed Albatrosses breeding at other localities. Using satellite transmitters, we identified two areas that were particularly favoured for foraging. Parents whose partners were brooding small chicks frequently moved north-east of PEI to shallow, productive waters where cold, nutrient-rich water upwells and results in enhanced levels of chlorophyll-a. By contrast, parents with older chicks that could be left unattended often foraged along the Agulhas Bank where eddies and shear forces promote vertical mixing. The at-sea distribution of birds breeding at PEI was located between those reported for Indian Yellow-nosed Albatrosses breeding at Ile Amsterdam and Atlantic Yellow-nosed Albatrosses ( T. chlororhynchos ) breeding at Gough Island, so that birds from these localities may face different threats at sea. Our study is the first to highlight key feeding areas for Indian Yellow-nosed Albatrosses from PEI and to demonstrate partitioning of foraging grounds by Yellow-nosed Albatrosses from different localities.